The effect of board characteristics and foreign ownership on firm performance in Nigeria - Isa, Usman (2017)
The global economic crisis has increased the focus on the role of board of directors in ensuring integrity and transparency in corporate reporting of companies world-wide. Board characteristics are crucial in an organisation saddled with the responsibility of making decisions and determining the ability of monitoring management in carrying out its responsibilities efficiently and effectively. Hence, this study aims to investigate the effect of board characteristics and foreign ownership on firm performance of non-financial listed companies in Nigeria. ROA and ROE are used to measure financial performance while the independent variables include: board size, board independence, audit committee size, audit committee independence, risk management committee and foreign ownership. The study used 122 firms listed on Nigerian Stock Exchange (NSE) for the year 2014 and 2015. Regression analysis was used to analyse the data. The results of the study revealed that larger board size affects ROA and ROE, while a higher proportion of independent directors has a positive impact on the performance of firms’ in Nigeria. Meanwhile audit committee size has a negative impact on ROA, but it is positively and significantly related to ROE. Independent audit committee shows a negative impact on ROA and ROE. Further, companies with a higher proportion of foreign investors and having a separate risk management committee are performing better and with higher returns. Therefore, the study recommends that policy makers and regulatory bodies should interpret this evidence as motivation for them to strengthen corporate boards’ practices to effectively deal with the unique features of corporate governance in emerging economies such as Nigeria